Pursuit Of Quality in Institutional Education – About Some Elements of Teacher’s Profi le in ISE-Based Developments - Mrázik, Julianna (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The Inclusive System of Education – latter as ISE – is a pedagogical framework aim of which is to equalize the differences between chances of the disadvantaged children in school. The essay focuses on both explicit and implicit profi le of the pedagogue and teacher-ethos of the ISE and ISE-based developments, on the fundament of special literature and by critical analyses of the guides. The study has examined the refl ection of the contemporary trends of the standardization of pedagogues’ competences as well as if the role of the teacher does exist in forefront of the ISE. The aim of the study was to present and characterizing the revealed teacher profi le; to reveal the possible defi cits and to estimate the probable ways of development of the foci. While reviewing the sources, it becomes apparent that the success of the program strongly depends on the role of the teacher and his/her role is crucial in such processes. It has also been revealed that teachers are less addressed in the question of importance and it is questionable whether the teachers can receive a support while meeting the expectations raised by the program.